Inclusive Institutions – a Precondition of Sustainable Development. A Comparative Analysis Between Romania and Poland - Socoliuc (Guriță), Oana-Ramona; Pohoață, Ion; Diaconașu, Delia-Elena (European Journal of Sustainable Development, 2020)
When trying to identify the sources of growth and sustainable development, institutions and their effectiveness are among the most important and powerful instrument required to explain the economic dynamics of countries all over the world. More precisely, those rules, formal or informal, political or economic, that foster the participation of the majority of people in activities able to ensure the allocation of resources to their most productive destinations are the ones that promote long-term prosperity. Their significance is becoming even more important when the particular case of transition economies is addressed. Consequently, the aim of this paper is to demonstrate that inclusive institutions (political and economic ones) are a prerequisite for the long-run development, mainly for emerging economies. Using an unique dataset of indicators that highlight the quality of economic and political institutions we have employed a VEC Model, variance decomposition and Granger causality analysis for Romania and Poland, in order to emphasize that, from a comparative perspective, each transition path towards the market economy has designed different rules of the game determining, thus, dissimilar development profiles. Keywords: Sustainable development, Transition economies, Institutions, Institutional performance